RELATION BETWEEN LIFE SATISFACTION AND GDP IN THE EUROPEAN UNION - Degutis, Mindaugas; Urbonavičius, Sigitas; Gaižutis, Algis (Ekonomika, 2010)
In the paper, relation between GDP and subjective well-being, expressed as personal life satisfaction is analysed. On the basis of the European Union data from 2000 to 2009, the so-called Easterlin’s paradox, which claims that life satisfaction stays flat in face of the increasing wealth of nations, is tested. The test is carried out using aggregated country level data on life satisfaction from a Standard Eurobarometer survey and GDP per capita data. Both the cross-country correlation and the within-country trends’ regression analyses show that the GDP level is positively related to the level of life satisfaction. Although the relation is particularly strongly expressed in Eastern European countries, it also stays positive in many more prosperous EU countries. Nevertheless, further studies on factors influencing the shape of relation are necessary to explain exceptions from the relation. The authors also suggest a possible necessity to find more sensitive indicators of life satisfaction to measure it more accurately in the future.